STRATEGI PENANGANAN BANJIR DI KAMPUNG BABAKAN BANDUNG DESA LEUWISADENG KECAMATAN LEUWISADENG - Derivan Sunarya; Edi Sutoyo (JPMUJ, 2023)
Flood is one of the natural disasters caused by overflowing sea or river water or excessive rain which causes land to be inundated with water. And currently there are many incidents that have experienced flooding in various regions of Indonesia including the village of Leuwisadeng. This has had a huge impact on society and various trade and economic sectors. Therefore this study aims to provide strategies or ideas or solutions for flood prevention so that they can inhibit flooding in the village of Leuwisadeng.